N‐Substituted 1, 2, 3‐Triazolyl‐Appended Indole‐Chalcone Hybrids as Potential DNA Intercalators Endowed with Antioxidant and Anticancer Properties. Issue 9 (5th March 2018) - Aneja, Babita; Arif, Rizwan; Perwez, Ahmad; Napoleon, John V.; Hasan, Phool; Rizvi, M. Moshahid A.; Azam, Amir; Rahisuddin,; Abid, Mohammad
Abstract: Despite the fact that many small molecule inhibitors have been approved for cancer therapy, we still have a mighty long road to traverse in the field of targeted therapy against cancer. In order to overcome the challenges of chemo resistance and selectivity, we designed and synthesized 1, 2, 3‐triazole appended indole‐chalcone derivatives (4 a‐q ) and evaluated their antioxidant, anticancer and DNA binding properties. Among all the analogs, compounds with o ‐chloro (4b ), o ‐fluoro (4h ) and p ‐fluoro (4j ) substitution exhibited potent antioxidant activity and the potency of4 b was comparable to the standard ascorbic acid. In a cell based screen, compound4 b inhibited the growth of human cervical cancer (SiHa) and colorectal epithelial carcinoma (SW620) cancer cell lines with an IC50 values of 67.99 and 48.96 μg mL −1, respectively without showing any significant cytotoxicity in human embryonic kidney cells (HEK293) at the similar concentration. To gain insight into the DNA‐binding ability, various spectroscopic techniques such as UV‐visible, fluorescence, circular dichroism, viscosity and cyclic voltametric studies were performed. These studies exposed that compounds4 b, 4 h and4 j act via non‐covalent intercalative mode of binding to DNA causing their antiproliferative activity, supported by molecular docking studies. Our study revealed the non‐toxic nature and potent activity of compound4 b makes it a suitable candidate for further optimization and pharmacological studies. Abstract : A series of N‐substituted 1, 2, 3‐triazolyl‐appended indole‐chalcone hybrids (4a‐q) were designed as anticancer and DNA intercalators. The study suggests hybrid compound with o ‐chloro substituent (4b ) as suitable candidate for further structure activity relationship (SAR) and pharmacological evaluation.